CLINICAL STUDY ON CHURNA BASTI ADMINISTERED IN MODIFIED KALA BASTI SCHEDULE IN AMAVATA - Rajan, *Amritha; Ashvini, M Kumar; Lohith, B A (International Journal of Ayurveda and Pharma Research, 2016)
Amavata is most common debilitating joint disorder which makes the life of patient almost crippled. Amavata in the modern parlance can be correlated with Rheumatoid Arthritis which is a highly prevalent disease in the present life scenario due to the changing dietetic habits, social structure, environmental and mental stress. Ayurveda has a lot to offer in this regard. The Chikitsa explained for Amavata includes Shodhana as well as Shamana which includes Langhana, Deepana, Swedana, Virechana, Snehapana, Basti and Upanaha. Therefore, the study was planned to evaluate the efficacy of Churnabasti in modified Kalabasti schedule in the management of Amavata. Churna Basti yoga explained by Acharya Chakrapani comprises of drugs possessing Ushna & Teekshnagunas, Deepana-Pachana, Vata Kaphahara and Shula-Shothahara properties which may help in attaining Agnideepti, Laghutva, Nirama Lakshana and Shoolahara effect. Combination of Vaishwanara choorna, Rasna Saptaka Kashaya and Dhanyamla administered in Amavata is yielding beneficial effects as the ingredients possess the properties opposite to that of Amavata and therefore acts positively on the disease. The present study was planned based on this concept and statistically highly significant effects (P>0.0001) were observed in the various assessment parameters of Amavata such as Sandhishoola, Sandhishotha, Sandhistabdhata Sandhisparsa Asahyata etc. In overall effect of therapy maximum number of patients (40.12%) got marked improvement. Therefore, Churna Basti comprising of drugs possessing properties opposite to Ama can be considered as a good remedy in the management of Amavata.